Hubungan antara penerapan digital marketing dengan volume penjualan usaha pengolahan bakso ikan di Kota Kendari - Yuliana; Budiyanto; Piliana, Wa Ode; Siang, Roslindah Daeng; Patadjai, Andi Besse; Sriwulan, Desy (Universitas Halu Oleo, 2024)
The study was carried out in the city of Kendari, Southeast Sulawesi province in June to July 2021. The study aims to find out the connection between a digital application of marketing and the volume of the fish meatball processing plant in the city of Kendari. Selective research location conducted. The population in this study is the owner of the meatball processing plant in the town of Kendari. Data obtained through interviews based on questionnaires. Data collected on the identity of respondents, the number of digital media/media used marketing, and the volume of sales. The data analysis used in this study is a coefficient correlation analysis. Analysis shows that between the variables of digital application of marketing (x) and the variable volume of sales (y) has a correlation coefficient value of 0,891 which means both variables are high correlation. This shows that the higher the application of digital marketing, the volume of the fish ball processing industry in the city of Kendari will increase.